Implementation Intentions for Physical Activity Behavior in Older Adult Women: An Examination of Executive Function as a Moderator of Treatment Effects. Issue 1 (6th February 2014) - Hall, Peter A.; Zehr, Christopher; Paulitzki, Jeffrey; Rhodes, Ryan
Abstract: Background: Implementation intentions are effective for enhancing physical activity, but it is unknown how well these effects extend to older adults and/or are modified by cognitive variables. Purpose: Our objective is to examine (1) the efficacy of an implementation intentions intervention for physical activity in older adult women and (2) to examine the moderating effects of executive function. Methods: Participants ( N = 75, M age = 73.72) completed measures of executive function and were randomly assigned to weekly implementation intentions for physical activity (experimental condition), implementation intentions for an unrelated behavior (control condition), or no treatment. Baseline activity was measured by accelerometer and self-report; follow-up activity was measured by weekly self-report. Results: Findings indicated a significant treatment effect for the experimental condition and a treatment by executive function interaction. Specifically, participants with relatively stronger executive function benefited most from the experimental intervention. Conclusions: Implementation intentions are effective for enhancing physical activity among older adult women, and the effects may be especially pronounced for those with relatively stronger executive function.